Manajemen Pemberian Pakan Pada Sapi Potong Di Balai Inseminasi Buatan Lembang Kabupaten Bandung Barat - Fajarwati, Aliana Bekti; Tri Budiarto; Nurulhaq, Muhammad Iqbal (Jurnal Ilmu Peternakan Indonesia, 2025)
The main focus included identifying feed types, determining efficient forage and concentrate feed weights, and monitoring weight gain in beef cattle. Data were collected through direct observation and measurements on a sample of 23 beef cattle. The results indicated that the feeds used included forage (elephant grass and corn stalks), concentrate (Hi-Pro-Vite 563B), and additional feeds (hay, bean sprouts, mineral blocks). Feeding was carried out systematically, considering frequency (three times for forage, twice for concentrate) and timing. Administering concentrate prior to forage proved beneficial to the digestive performance. The average weight gain of beef cattle was influenced by feed efficiency based on dry matter intake proportions. Good feed management was shown to increase productivity and reduce maintenance costs for beef cattle.